CLUSTER ANALYSIS AS A TOOL FOR DEVELOPING A PSYCHO-CORRECTIVE PROGRAM FOR MARRIED COUPLES IN EXTREME SITUATIONS. - Vashchenko, Olena (Sworld-Us Conference proceedings, 2025)
The work presents the results of an empirical study aimed at studying the peculiarities of marital conflicts in pairs, which are in extreme living conditions, in particular in the situation of military events. Cluster analysis was applied to highlight the